Measuring organizational performance. A review of the dimensions of hospital performance indicators. (13th November 2019) - Carini, E; Pezzullo, A M; Frisicale, E M; Cacciatore, P; Pilla, A Di; Grossi, A; Gabutti, I; Cicchetti, A; Boccia, S; Specchia, M L
Abstract: : Patients' increasing needs and expectations demand for an overall assessment of hospital performances. Several Agencies described sets of performance indicators and there is not a unanimous classification. The ImpactHTA Horizon2020 Project wants to address this aspect, developing a toolkit of key indicators to measure hospital organizational performance. The aim of this review is to identify the dimensions of quality in which hospital performance indicators are grouped, and to assess if there has been an evolution over time of the above-mentioned dimensions. Following the PRISMA statement, PubMed, Ovid and Web of Science databases were queried to perform an umbrella review. Articles focusing on secondary care settings, published January 2000-May 2018 were considered. The study design included was systematic review. 3680 records were screened and 6 systematic reviews ranging 2002-2014 were included. The following dimensions were described in at least 50% of the studies: 6 studies classified efficiency (53 indicators analyzed); 5 studies classified effectiveness (12 indicators), patient centeredness (10 indicators) and safety (8 indicators); 3 studies responsive governance (2 indicators), staff orientation (8 indicators) and timeliness (4 indicators). 3 reviews did not specify the indicators related to the dimensions listed, 1 gave a complete definition of the meaning of each dimension and related indicators. The research shows steady awareness of the importance of patient centeredness, effectiveness, efficiency, and safety dimensions; apparently, there is still not much attention to sustainability, appropriateness and accessibility in terms of indicators measuring, although those dimensions are described in one of the latest review. Another review described a new dimension, resources and capacity, which focuses on the availability of new technologies, underlining the growing importance of the adoption of digitalization in healthcare. Key messages: Main dimensions of performance indicators: efficiency, effectiveness, patient centeredness, safety. More emphasis to sustainability and appropriateness to align with today's healthcare challenges.